1996
DOI: 10.1152/ajpheart.1996.270.6.h2021
|View full text |Cite
|
Sign up to set email alerts
|

Relation between contractile function and regulatory cardiac proteins in hypertrophied hearts

Abstract: The aim of this study was to examine the mechanism(s) underlying the reduced isoproterenol-induced positive inotropic and lusitropic effects in hypertrophied hearts. Chronic beta-adrenergic stimulation (2.4 mg isoproterenol.kg-1. day-1 for 4 days) induced cardiac hypertrophy by 33 +/- 2% in rats. A parallel downregulation of phospholamban (PLB) and sarcoplasmic reticulum Ca2(+)-ATPase (SERCA2) protein expression by 49 and 40%, respectively, was observed, whereas troponin I (TNI) and C protein remained unchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 0 publications
3
29
1
4
Order By: Relevance
“…Many β-blocker-associated gene expression changes in responders versus nonresponders represent a partial reversal of the cardiac fetal/adult gene program, 3,34,35 but they may also be consistent with alternative regulatory mechanisms including inhibition of β 1 -AR signaling 5,6,36 or enhanced thyroid hormone receptor (TR-α) activity (Table 5). 7 We previously reported changes in TR-α1 and TR-α2 expression in IDC LVs consistent with hypothyroidism at the TR-α level.…”
Section: Figure 3 Continuedmentioning
confidence: 99%
“…Many β-blocker-associated gene expression changes in responders versus nonresponders represent a partial reversal of the cardiac fetal/adult gene program, 3,34,35 but they may also be consistent with alternative regulatory mechanisms including inhibition of β 1 -AR signaling 5,6,36 or enhanced thyroid hormone receptor (TR-α) activity (Table 5). 7 We previously reported changes in TR-α1 and TR-α2 expression in IDC LVs consistent with hypothyroidism at the TR-α level.…”
Section: Figure 3 Continuedmentioning
confidence: 99%
“…Because several of these PDEs are also targets of cGMP, it is possible that cGMP may affect cardiac hypertrophy indirectly through modulation of the activity of these PDEs (24), which regulate cAMP levels and, thereby, associated aspects of cardiac contractility. For example, protein kinase A (PKA)-dependent modulation of the L-type calcium channel, cardiac ryanodine receptor, sarcoplasmatic reticulum Ca 2+ -ATPase (SERCA) (25)(26)(27)(28), and calcium has been implicated in cardiac hypertrophy induced by the stimulation of β-adrenergic receptors (β-ARs) (29)(30)(31).…”
mentioning
confidence: 99%
“…There is considerable controversy about the BP changes due to the ISO-induced cardiac injury. Multiple studies have demonstrated declined pumping ability of the heart (Lin, 1973;Baldwin et al, 1982) and depressed contractile ability of the heart in ISO-induced hypertrophy (Vassallo et al, 1988;Bowling et al, 1990;Stein et al, 1996), while others reported contractile function enhancement (Cihak et al, 1992;Tang and Taylor, 1996;Arthur and Belcastro, 1997). In the present study, rats with hypertrophic hearts exhibited significant elevation in both systolic and diastolic BP, which is in agreement with Papparella et al (2008), who reported increased BP in angiotensin-II-treated rats.…”
Section: Discussionmentioning
confidence: 99%